Maternal social support and resilience in caring for preterm newborns at the neonatal intensive care unit (NICU): A qualitative study - Sabina Eduku; Emma Annan; Mary Ani Amponsah (Heliyon, 2024)
Introduction: Mothers with preterm babies at the NICU are at a high risk of acquiring psychological distress as a result of unexpected and upsetting experiences. While there is a strong emphasis on the infant's health, the mother's well-being, particularly her mental health, is sometimes disregarded. A qualitative exploratory descriptive design was used to explore maternal social support and resilience in caring for preterm newborns at the NICU in Municipal hospital in Ghana from May to July 2022. Methods: A qualitative exploratory method was used, and a purposive sampling technique was used to select 15 postnatal women who had their preterm babies on admission to the NICU until data saturation. Data was analysed using thematic content analysis. Results: The findings of the study showed that social support for their mothers as they care for their preterm infants contributed to their resilience. Three themes emerged from the analysis of the data: informational support, instrumental support and psychosocial support. Conclusion: There is a need for training in communication skills and counselling for healthcare professionals working in the NICU to be able to communicate effectively with mothers and also adopt a family-centered approach in the care of preterm infants. This will support mothers to strengthen their resilience when caring for their premature babies in the NICU. The role of instrumental support for mothers specifically financial and physical care support in building maternal resilience cannot be overemphasised.